Procedura skutecznego wdrażania outsourcingu usług logistycznych - Kocot, Damian (A Procedure of Effective Introduction of Logistic Services' Outsourcing, 2008)
The article is the test of checking the stages of the implementation of logistic services outsourcing. The thesis is proposed that the condition of correct usage of outsourcing is observing the suitable sequence of its implementation. The essence of outsourcing and the chances of its usage are presented. The suitable sequence of implementation of logistic services is showed in the next part of the article.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 11, s. 292-301